A newly designed laser-based time- and angle-resolved photoelectron spectroscopy with a time-of-flight electron analyzer - Shengyue Lu; Yeqinbo Zhang; Jingze Li; Xueyan Ma; Yongkai Deng; Yunquan Liu (AIP Advances)
Angle-resolved photoemission spectroscopy can directly detect the energy and momentum resolved electronic structure of solids, serving as a central role in the discovery and understanding of quantum materials. Here, we report the development of a novel time-resolved ARPES setup equipped with a table-top vacuum ultraviolet laser source with a photon energy of 10.8 eV and a time-of-flight analyzer. The light source is obtained through the generation of ninth harmonics of a 1030 nm Yb fiber-based amplified laser (290 fs, 100 μJ). The photon flux can reach 5 × 1012 photons/s at 333 kHz. We demonstrate its performance in ARPES measurements of the polycrystalline gold film and the electronic structure of the topological insulator Bi2Te3. By introducing a pump beam, we make a pump–probe experiment to detect unoccupied electronic states of Bi2Te3. This setup can achieve an energy resolution of 21.6 meV and a temporal resolution of 296 fs with the tunability of the polarization and repetition rates. This system can provide an important platform to study the non-equilibrium band structure of complex quantum materials with exceptional energy resolution at high repetition rates.